BF0801, a novel adenine derivative, inhibits platelet activation via phosphodiesterase inhibition and P2Y12 antagonism - Zhang, Si; Hu, Liang; Du, Hongguang; Guo, Yan; Zhang, Yan; Niu, Haixia; Jin, Jianguo; Zhang, Jian; Liu, Junling; Zhang, Xiaohui; Kunapuli, Satya P.; Ding, Zhongren (Thrombosis and Haemostasis, 2010)
Though antiplatelet drugs are proven beneficial to patients with coronary heart disease and stroke, more effective and safer antiplatelet drugs are still needed. In this study we report the antiplatelet effects and mechanism of BF0801, a novel adenine derivative. BF0801 dramatically inhibited platelet aggregation and ATP release induced by ADP, 2MeSADP, AYPGKF, SFLLRN or convulxin without affecting shape change in vitro. It also potentiated the inhibitory effects of adenosine-based P2Y12 antagonist AR-C69931MX or phosphodiesterase (PDE) inhibitor IBMX on platelet aggregation. The cAMP levels in both resting and forskolin-stimulated platelets were increased by BF0801 suggesting its PDE inhibitor activity, which is further confirmed by the concentration-dependent suppression of BF0801 on the native and recombinant PDE. Similar to AR-C69931MX, BF0801 drastically inhibited 2MeSADP-induced adenylyl cyclase inhibition in platelets indicating its P2Y12 antagonism activity, which is substantiated by the inhibition of BF0801 on the interaction between ADP and P2Y12 receptor expressed in CHO-K1 cells measured by atomic force microscopy. Moreover, we confirmed the antiplatelet effects of BF0801 using platelets from rats intravenously given BF0801. In summary, for the first time we developed a novel adenine derivative bearing dual activities of PDE inhibition and P2Y12 antagonism, which may have therapeutic advantage as a potential antithrombotic drug.
Keywords: Antiplatelet; adenine derivative; cAMP; P2Y12; phosphodiesterase